(untitled) (Bangladesh Journal of Animal Science, 2020)
This study was conducted to observe the effect of different administration method of garlic and neem on growth performances, feed efficiency and serum biochemical parameters for safe broiler production. The experiment was done for a period of 32 days with 384 one-day-old straight run broiler chicks. The broiler chicks were divided into six groups each of 64 birds and replicated to four subgroups each of 16 birds. The dietary groups were; control (basal diet; no additives), antibiotic (basal diet + antibiotic), garlic in feed (basal diet + 0.25% garlic powder), garlic in water (basal diet + garlic extracts), neem in feed (basal diet + 0.25% neem powder) and neem in water (basal diet + neem extracts). Results showed that the body weight and body weight gain increased significantly (P<0.05) in both the garlic and neem groups compared to the control group. Feed intake was not different (P>0.05) among the treatment groups. Garlic in feed and water and neem in feed groups showed better FCR (P<0.05) compared to the other treatment groups. There were no significant (P>0.05) difference in meat yield, bone development and dressing parameters except head and gizzard in different dietary groups. Supplementation of garlic with feed and water significantly (P<0.05) decrease cholesterol, triglyceride and LDL compared to the other groups. However, both the garlic and neem groups showed numerically higher HDL compare to the control group. There were no 0significant (P>0.05) differences in serum glucose and GPT among different treatment groups. GOT was significantly (P<0.05) lower in neem groups than that of garlic and antibiotic groups. Additive groups showed higher profitability than control group. Based on the results of the study, it may be suggested that the garlic and neem could be used both in feed and water as potential feed additives for safe broiler production. Bang. J. Anim. Sci. 2019. 48 (2): 116-126